Friendship, Courage, and Conflict in Harry Potter and the Sorcerer’s Stone (2001): A Dramatic Analysis - Tustia Wulan Dewi; Tri Devi Dian Lestari (TEKILA: Journal of Language Teaching and Literature, 2024)
This study presents an analysis of character development and narrative conflict in the film Harry Potter and the Sorcerer’s Stone (2001), directed by Chris Columbus and based on the novel by J.K. Rowling. The purpose of this study is to examine how the main characters, conflicts, and themes contribute to the development of the narrative and the delivery of moral messages in the film. The research employs a qualitative descriptive approach using narrative analysis to interpret scenes, dialogues, and character actions presented in the film. The findings show that the main characters Harry Potter, Hermione Granger, and Ron Weasley demonstrate significant character development throughout the story. Harry develops from an insecure and passive child into a courageous and responsible individual, while Hermione and Ron contribute to the narrative through their intelligence, loyalty, and cooperation. The study also finds that the central conflict involving Lord Voldemort’s attempt to obtain the Philosopher’s Stone functions as the primary narrative driver that shapes the progression of the plot. In addition, several key themes are identified, including friendship, courage, moral choice, and sacrifice. These themes are conveyed through character interactions, important scenes, and symbolic elements within the film. Overall, the analysis indicates that Harry Potter and the Sorcerer’s Stone not only provides an engaging fantasy narrative but also communicates important moral values related to cooperation, responsibility, and ethical decision-making.